The developing person through childhood - Berger, Kathleen Stassen (New York, NY : Worth, 2000)
The beginnings. The first 2 years: infants and toddlers. The play years. The school years.
Keywords: Psychology; Child psychology; Child development; Child psychology; Infants -- Development; Infant psychology